2023
DOI: 10.1093/mnras/stad273
|View full text |Cite
|
Sign up to set email alerts
|

The photometric periods of rapidly rotating field ultra-cool dwarfs

Abstract: We use 1-m class telescopes and the Transiting Exoplanet Survey Satellite (TESS) to explore the photometric variability of all known rapidly rotating (vsin i ≳ 30 km s−1) ultra-cool (≥M7) dwarfs brighter than I ≈ 17.5 mag. For a sample of 13 M7–L1.5 dwarfs without prior photometric periods, we obtained I-band light curves with the SMARTS 1.3m and WIYN 0.9m telescopes and detected rotation-modulated photometric variability in three of them. Seven of our targets were also observed by TESS and six of them show si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We interpret these as ECMI emission and refer to these two bursts as B1 and B2 hereafter. The time interval between the bursts' maxima is 2.70 ± 0.02 hours, which is close to (but different from) the rotation period [2.84140 ± 0.00039 hours (15)]. The right circularly polarized (RCP) emission varies slowly during the observation, reaching a maximum before the bursts occur.…”
Section: Radio Observations Of Lsr J1835+3259mentioning
confidence: 66%
See 1 more Smart Citation
“…We interpret these as ECMI emission and refer to these two bursts as B1 and B2 hereafter. The time interval between the bursts' maxima is 2.70 ± 0.02 hours, which is close to (but different from) the rotation period [2.84140 ± 0.00039 hours (15)]. The right circularly polarized (RCP) emission varies slowly during the observation, reaching a maximum before the bursts occur.…”
Section: Radio Observations Of Lsr J1835+3259mentioning
confidence: 66%
“…On 15 June 2021, we observed the brown dwarf (spectral type M8.5) LSR J1835+3259 (also cataloged as 2MASS J18353790+3259545) using the European VLBI Network (EVN). LSR J1835+3259 exhibits a rapid rotation [rotational period 2.84140 ± 0.00039 hours ( 15 )] and is at a distance of 5.6885 ± 0.0015 parsecs ( 16 ) from Earth. Previous studies have shown that it has strong radio emission in both the bursting and quiescent components ( 3 , 9 , 17 19 ).…”
Section: Radio Observations Of Lsr J1835+3259mentioning
confidence: 99%